Visualizable vs. standard, non-visualizable steerable sheath for pulmonary vein isolation procedures: Randomized, single-centre trial - Janosi, Kristof; Debreceni, Dorottya; Janosa, Benedek; Bocz, Botond; Simor, Tamas; Kupo, Peter (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Steerable sheaths (SSs) are frequently used to improve catheter contact during pulmonary vein isolation (PVI) procedures. A new type of visualizable (by electroanatomical mapping system) SS has become available in clinical treatment. Purpose: We aimed to compare procedural data of visualizable vs. non-visualizable steerable sheath assisted PVI procedures in patients with atrial fibrillation (AF). Methods: In this single-centre randomized study, we enrolled a total of 100 consecutive patients who underwent PVI due to AF. Results: A total of 100 patients were randomized into 2 groups (visualizable SS group: 50; non-visualizable SS group: 50) . Acute ablation success was 100% and the rate of the first pass isolation were similar (92% vs. 89%; p=0.88). Using visualizable SS, left atrial (LA) procedure time (53.1 [41.3; 73.1] min vs. 59.5 [47.6; 74.1] min.; p=0.04), LA fluoroscopy time (0 [0; 0] s vs. 17.5 [5.5; 69.25] s; p<0.01) and LA fluoroscopy dose (0 [0; 0.27] mGy vs. 0.74 [0.16; 2.34] mGy; p<0.01) was significantly less, however there was no difference in the total procedural time (90 ± 35.2 min vs. 99.5 ± 31.8 min; p=0.13), total fluoroscopy time (184 ± 89 s vs. 193 ± 44 s; p=0.79), and total fluoroscopy dose (9.12 ± 1.98 mGy vs. 9.97 ± 2.27 mGy; p=0.76). Compared to standard, non-visualizable SS group, the number of radiofrequency ablations was fewer (69 [58; 80] vs. 79 [73; 86); p<0.01) as well as total ablation time was reduced (1049 sec. [853; 1175] vs. 1265 sec. [1085; 1441]; p<0.01) in the visualizable SS cohort. No major complications occurred in either group. Conclusion: Compared to the standard, non-visualizable SS, visualizable SS significantly reduces the left atrial procedure time, RF delivery and fluoroscopy exposure without compromising its safety or effectiveness in patients undergoing PVI procedures for AF.